Identifying a deletion affecting total lung capacity among subjects in the COPDGene study cohort - Begum, Ferdouse (Genet Epidemiol, 2015)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive disease with both environmental and genetic risk factors. Genome-wide association studies (GWAS) have identified multiple genomic regions influencing risk of COPD. To thoroughly investigate the genetic etiology of COPD, however, it is also important to explore the role of copy number variants (CNVs) since the presence of structural variants can alter gene expression and can be causal for some diseases. Here, we investigated effects of polymorphic CNVs on quantitative measures of pulmonary function and chest CT phenotypes among subjects enrolled in COPDGene, a multi-site study. COPDGene subjects consist of roughly one-third African-American and two-thirds Non-Hispanic white adult smokers (with or without COPD). We estimated CNVs using PennCNV on 9,076 COPDGene subjects using Illumina's Omni-Express genome-wide marker array. We tested for association between polymorphic CNV components (defined as disjoint intervals of copy number regions) for several quantitative phenotypes associated with COPD within each racial group. Among African-Americans, we identified a polymorphic CNV on chromosome 5q35.2 located between two genes (FAM153B and SIMK1, but also harboring several pseudo-genes) giving genome-wide significance in tests of association with total lung capacity as measured by chest CT scans. This is the first study of genome-wide association tests of polymorphic CNVs and total lung capacity. While the ARIC cohort did not have the phenotype of total lung capacity, we found similar counts of CNV deletions and amplifications among African-American and European subjects in this second cohort.